Lifelong Citizenship: Integrating Ecological Values Into Podcaster-Based Digital Learning - Dedy Ari Nugroho; Eny Kusdarini; Awanis Akalili; Marzuki; Hazrat Shah Kayen (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2026)
The principle of lifelong citizenship plays a crucial role in fostering citizens' ecological awareness and responsibility in the digital age. This study aims to integrate lifelong citizenship values through podcast technology in ecological citizenship learning. The research method employed a qualitative approach with a case study design, implemented in the Wetland Environmental Citizenship course in the Civics Study Program at Universitas Lambung Mangkurat. Respondents comprised four lecturers and 12 students, selected through purposive sampling. Data were collected through in-depth interviews, observation, and document analysis, and validated using source triangulation and member checking. Data analysis was conducted interactively through the stages of data condensation, data presentation, and conclusion drawing. The results showed that using podcast media provides flexibility, creativity, and active student involvement in critically understanding citizenship and environmental issues. Podcast-based learning strengthens students' character as reflective, participatory, and sustainable ecological citizens, which aligns with the principle of lifelong citizenship.